the Impact of the Harmonious Comprehensive Learning Strategy on Developing Certain Coordinative Abilities and Performing Basketball Skills for Fifth-Year Preparatory Female Students (Damu Journal of Sport Sciences, 2025)
This study aims to explore the impact of the harmonious comprehensive learning strategy on developing certain coordinative abilities and the performance of basic basketball skills among fifth-year preparatory female students. The researcher emphasized the importance of sports in students' lives, highlighting their role in enhancing physical fitness, mental health, and social interaction. Basketball, as a team sport, requires diverse coordinative skills such as motor estimation, quick response, and effort exertion, alongside basic skills like passing, dribbling, and shooting .The research problem arose from the observed difficulty among students in acquiring basic basketball skills, which negatively affected their self-confidence and active participation in sports activities. To address these challenges, the researcher proposed the use of the harmonious comprehensive learning strategy .The experimental method, employing two equivalent groups, was adopted. The study demonstrated the effectiveness of the harmonious comprehensive learning strategy in developing coordinative abilities such as motor estimation and quick response and in improving the performance of basic skills like dribbling, passing, and shooting. This underscores the success of implementing this strategy in achieving educational and athletic objectives.